Pharmacological Properties of Chalcones: A Review of Preclinical Including Molecular Mechanisms and Clinical Evidence - Salehi, Bahare; Quispe, Cristina; Chamkhi, Imane; El Omari, Nasreddine; Balahbib, Abdelaali; Sharifi-Rad, Javad; Bouyahya, Abdelhakim; Akram, Muhammad; Iqbal, Mehwish; Docea, Anca Oana; Caruntu, Constantin; Leyva-Gómez, Gerardo; et al. (Frontiers in Pharmacology, 2021)
Chalcones are amongst the leading bioactive flavonoids with a therapeutic potential implicated to an array of bioactivities investigated by a series of preclinical and clinical studies. In this article, different scientific databases were searched to retrieve studies depicting the biological activities of chalcones and their derivatives. This review comprehensively describes preclinical studies on chalcones and their derivatives describing their immense significance as antidiabetic, anticancer, anti-inflammatory, antimicrobial, antioxidant, antiparasitic, psychoactive and neuroprotective agents. Besides, clinical trials revealed their use in the treatment of chronic venous insufficiency, skin conditions and cancer. Bioavailability studies on chalcones and derivatives indicate possible hindrance and improvement in relation to its nutraceutical and pharmaceutical applications. Multifaceted and complex underlying mechanisms of chalcone actions demonstrated their ability to modulate a number of cancer cell lines, to inhibit a number of pathological microorganisms and parasites and to control a number of signaling molecules and cascades related to disease modification. Clinical studies on chalcones revealed general absence of adverse effects besides reducing the clinical signs and symptoms with decent bioavailability. Further studies are needed to elucidate their structure-activity, toxicity concerns, cellular basis of mode of action and interactions with other molecules.